2008
DOI: 10.1002/ana.21342
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐specific alterations of glutamate receptor expression in tuberous sclerosis complex cortical tubers

Abstract: Objective-Genetic loss of TSC1/TSC2 function in tuberous sclerosis complex (TSC) results in overactivation of the mammalian target of rapamycin complex 1 pathway, leading to cellular dysplasia. We hypothesized that the dysplastic cells in TSC tubers are heterogeneous, including separable classes on a neuronal-glial spectrum, and that these dysplastic cells express glutamate receptor (GluR) patterns consistent with increased cortical network excitability.Methods-Surgically resected human cortical tubers and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
141
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(155 citation statements)
references
References 51 publications
13
141
0
1
Order By: Relevance
“…The giant cells in TSC are histologically similar to balloon cells detected in FCD type IIb in that they exhibit an enlarged cell body and opalescent, glassy-appearing, eosinophilic cytoplasm [6]. Both giant cells and balloon cells express cell proteins characteristic of neuroglial progenitor cells such as SOX2, nestin, vimentin, and c-myc, suggesting a failure to differentiate prior to migration into the cortex [137,[191][192][193]; for reviews see [117] and [185]). With the recent advances in both fetal ultrasonography and magnetic resonance imaging, tubers can be detected during the prenatal period in TSC patients [194][195][196].…”
Section: Clinical and Neuropathologic Featuresmentioning
confidence: 94%
See 1 more Smart Citation
“…The giant cells in TSC are histologically similar to balloon cells detected in FCD type IIb in that they exhibit an enlarged cell body and opalescent, glassy-appearing, eosinophilic cytoplasm [6]. Both giant cells and balloon cells express cell proteins characteristic of neuroglial progenitor cells such as SOX2, nestin, vimentin, and c-myc, suggesting a failure to differentiate prior to migration into the cortex [137,[191][192][193]; for reviews see [117] and [185]). With the recent advances in both fetal ultrasonography and magnetic resonance imaging, tubers can be detected during the prenatal period in TSC patients [194][195][196].…”
Section: Clinical and Neuropathologic Featuresmentioning
confidence: 94%
“…For example, large-scale gene expression studies indicate alterations in glutamatergic and GABAergic synaptic transmission in cortical tubers, involving reduced expression of the glial glutamate transporter (GLT-1 or EAAT2), reduced expression levels of GABA A receptor subunits, and reduced expression of potassium channels [135]. Selective alterations of iGlu subunits, as well as of mGluR subtypes (with prominent group I mGluR expression, mGluR1, and mGluR5) have been reported in tubers [193,223,224]. In addition (as discussed above) an excitatory action of GABA has been reported in TSC [162].…”
Section: Epileptogenesismentioning
confidence: 99%
“…Numerous studies have shown activated mTORC1 substrates phospho-p70S6 kinase, phospho-S6, and phospho-4E-BP1 in resected and postmortem TSC tuber samples (Baybis et al 2004;Miyata et al 2004;Talos et al 2008). Indeed, two recent studies have shown mTORC1 activation in fetal tubers (Tsai et al 2012;Prabowo et al 2013).…”
Section: Focal Cortical Dysplasia and Tuberous Sclerosis: Paradigm Mtmentioning
confidence: 99%
“…TSC cortical tubers exhibit disrupted neuronal laminar architecture, hypomyelination, and the hallmark enlarged, undifferentiated, "balloon-like" giant cells (7,8), as well as dysmorphic and enlarged neurons, hypertrophic astrocytes, and a variety of reactive cells (9)(10)(11). Severe epilepsy is seen in most patients with TSC, and the number and size of tubers correlate with an increased risk for intractable seizures (3,5), which are associated with poor cognitive outcome (6).…”
mentioning
confidence: 99%